Loneliness of the Blind and the Visually Impaired - Ami Rokach; David Berman; Alison Rose (Frontiers in Psychology, 2021)
Loneliness has been termed a social epidemic, especially when experienced by people with disabilities. In order to better understand how loneliness is experienced in vulnerable populations, the present study compared the qualitative dimensions of loneliness of the blind and visually impaired with the general population not on the frequency or intensity of their loneliness, but on its qualitative aspects. One hundred and eighty-seven participants responded to a questionnaire which measured the qualitative aspects of loneliness on five subscales: Emotional distress, social inadequacy, Growth and discovery, social isolation, and emotional alienation. Results indicated that as expected, the two populations differed significantly in their scores on four of the five subscales (except emotional alienation), but in the opposite direction of what was expected. That may indicate that the visually impaired person’s ability to transcend their blindness, and connect with those around them, and the larger society, in different—and not necessarily less meaningful-manner than the seeing general population. As expected, the visually impaired scored significantly higher than the general population on the Growth and development subscale.